Successful Visual Training for a Presbyopic Patient Following Unsuccessful Prism Therapy - Roberston, K M (Canadian Journal of Optometry, 1983)
Orthoptic therapy was instituted on a presbyopic patient having convergence insufficiency. The combination of presbyopia and convergence insufficiency has often suggested a poorer prognosis. Prism therapy had been attempted previously and the measurement over ten years indicated some form of prism adaptation as well as reduced measured fusional reserves. During visual training and after cessation of visual training the increased positive fusional vergences were monitored and recorded.